Recognition of Mesoscalpellum Hoek, 1907 sensu Newman & Ross, 1971 (Cirripedia: Scalpellidae: Scalpellinae) as a valid genus: a novel approach using ontogenetic patterns in the classification of scalpellid barnacles - Shalaeva, Kate; Boxshall, Geoff (Zootaxa, 2024)
Our ability to reconstruct the evolutionary history of deep-water scalpellid barnacles (Crustacea: Cirripedia: Scalpellidae) and to understand their geographical distributions and ecology, is limited by the lack of a robust classification system. Analysis of the ontogeny of scalpellids highlights the significant morphological changes that occur during development from the smallest, recently settled juveniles up to full-grown specimens. Externally, these ontogenetic alterations can include changes in size, shape, and in the capitulum/peduncle ratio, as well as changes in the shape of plates resulting from modifications in the patterns of calcification. Using an exemplar developmental series of Mesoscalpellum carinatum (Hoek, 1881), we reveal how the misinterpretation of such changes has resulted in the recognition of polyphyletic and paraphyletic taxonomic units and how this has impacted all previous classifications proposed for the Scalpellidae. Our study explores a novel approach to the recognition of Mesoscalpellum Hoek, 1907 sensu Newman & Ross, 1971 as a monophyletic unit, based on the incorporation of data derived from developmental patterns. The re-establishment of this genus leads to significant systematic rearrangement. Multiple taxa currently placed in three scalpellid subfamilies and five genera were recognised as synonyms of just three Mesoscalpellum species—M. carinatum (Hoek, 1881), Mesoscalpellum sanctaebarbarae (Pilsbry, 1907) and Mesoscalpellum japonicum (Hoek, 1883). Two scalpellid genera, Barbascalpellum Zevina, 1978 and Pteroscalpellum Zevina, 1978, are no longer regarded as valid. In future, if study of scalpellid developmental series demonstrates that the holotype of a species is ambiguous and cannot be used for the precise application of the name of a taxon, a level of type status should be assigned to the full-grown specimen to promote its use for comparative study. We suggest that our perspective will help to resolve the confusion around the traditional typological grouping of other scalpellid genera and will foster the creation of a robust scalpellid classification.